PENERAPAN PIDANA TERHADAP PELAKU PERAMBAHAN HUTAN DIKABUPATEN LOMBOKTIMUR (STUDI DI KECAMATAN SUWELA, DINAS KEHUTANAN DAN SUMBER DAYA ALAM) - MASYHUR MASYHUR (GANEC SWARA, 2023)
The purpose of this study is to determine the application of Law No. 41 of 1999 in dealing with forest encroachment in East Lombok Regency and to determine the factors that influence the ineffective implementation of Law No. 41 of 1999 concerning forest encroachment in East Lombok Regency. While the research method of this writing includes non-doctrinal legal research, while judging from the form of this research is a diagnostic research, which is a research that is intended to obtain information regarding the causes of a symptom or several symptoms, judging from the nature of this research, it is a descriptive research. , which is intended to provide data that is researched as thoroughly as possible about humans, circumstances or other symptoms. From the results of research and interviews, it is concluded that the obstacles and problems in law enforcement against forest encroachment are found in various stages, namely looking at the factors of law enforcement officers, it will be related to aspects of the quality and quantity of the law enforcement officers. Meanwhile, quality is related to the ability or professionalism of law enforcement officers in handling forestry cases, especially forest encroachment. Weaknesses in terms of quality and quantity of law enforcement officers will have a very large influence in dealing with criminal acts of forest encroachment.